Interaction between Neisseria gonorrhoeae bacterial peroxidase and its electron donor, the lipid-modified azurin - Nóbrega, Cláudia S. (2021)
cofinanced by the ERDF under the PT2020 Partnership Agreement (POCI-01-0145-FEDER-007728).